The life of a matriarch : a social history of Nyonyas in British Singapore, 1880-1940 - Yew, Charmaine Qian Le (Nanyang Technological University, 2020)
The baba nyonya community, also known as the Straits Chinese, flourished in British colonial Singapore from the 1880s to 1940 due to their hybridized identity, which incorporated elements of Chinese, Malay and British cultures. The advantages reaped by Chinese baba men and their role in perpetuating this communal identity have been widely studied to justify their high socio-economic status under the British colonial administration. However, studies on Chinese nyonya women focused mainly on their material culture due to the gendered division of labor within a Straits Chinese household. Recent studies on nyonyas placed great emphasis on public schooling to suggest ideas of women’s emancipation under the British Colonial climate in Singapore. Hence, little attention was given to the role of nyonyas in perpetuating the Straits Chinese communal identity. This paper hence argues that due to the affluence of Straits Chinese households, Nyonyas tend to work within the patriarchal family system and exploit the power differentials between various family members by forging mutually dependent relationships. She ultimately emerges as a matriarch of her husband’s household, where she was an active agent in perpetuating the Straits Chinese identity in the domestic sphere in British Singapore from the 1880s to 1940.